A literature review study: Bridging global and local initiatives on domestic violence against women campaigns - Maidin, Anisafina; Sakrani, Siti Najah Raihan (Journal of Islamic, Social, Economics and Development, 2025)
Domestic violence against women remains a persistent and deeply rooted social issue. Unequal power relations, gendered norms and systemic barriers that restrict women’s access to safety and justice believe to be among the root causes. Over the years, awareness campaigns have emerged globally and locally as critical tools to challenge cultural silence, promote behavioural change and mobilise collective responsibility in addressing violence against women. Various initiatives have demonstrated the power of public campaigns in breaking the invisibility of abuse, amplifying survivors’ voices and shifting public discourse. Numerous efforts have played significant roles in strengthening public awareness, expanding support services and promoting community the engagement. These collaborative efforts are supported by the relevant stakeholder for example the federal as well as state government, NGOs and shelters homes. They work hand in hand and collectively under the framework of combating violence against women. This paper aims to provide a comprehensive review of domestic violence awareness campaigns targeting women, drawing from global experiences and Malaysia’s local landscape of advocacy and stakeholder involvement. The review offers insights contributing to effort in eliminating domestic violence against women globally.